The role of multimedia technologies in the modern education system - Михайленко, В. Л.; Федорченко, Руслана Анатоліївна; Сахарова, І. В.; Строгонова, Тетяна Василівна; Mykhaylenko, V.; Fedorchenko, R. A.; Sakharova, I.; Михайленко, В. Л.; Федорченко, Р. А.; Сахарова, И. В.; Строгонова, Т. В.; Strogonova, T. (Poland: W. Zukow, 2017)
In the modern education system there are rapid and significant changes that do not by pass the teaching of disciplines in medical universities. Different types of multimedia technologies allow you to model the conditions of learning activities and implement them in the form of various training exercises. Each of these types contributes to a more rational activity of the teacher at certain stages of the educational process, expands opportunities, intensifying the pedagogical process as a whole. Technological novelties help to activate self-motivation of students, their creative thinking, independence and the desire to comprehensively obtain and assimilate information, stimulate curiosity and interest in scientific activity. В современной системе образования происходят стремительные и значительные изменения, которые не обходят стороной и преподавание дисциплин в медицинских ВУЗах. Различные виды мультимедийных технологий позволяют моделировать условия учебной деятельности и реализовывать их в виде различных тренировочных упражнений. Каждый из указанных видов способствует более рациональной деятельности преподавателя на определенных этапах учебного процесса, расширяет возможности, интенсифицируя педагогический процесс в целом. Технологические новинки помогают активизировать самомотивацию студентов, их креативное мышление, самостоятельность и стремление к всестороннему получению и усвоению информации, стимулируют любознательность и интерес к научной деятельности. У сучасній системі освіти відбуваються стрімкі і великі зміни, які не обходять стороною і викладання профілактичних дисциплін у медичних вищих навчальних закладах. Різні види мультимедійних технологій дозволяють моделювати умови навчальної діяльності та реалізовувати їх у різноманітних тренувальних вправах. Кожен із вказаних видів сприяє більш раціональній діяльності викладача на певних етапах навчального процесу, розширює можливості, інтенсифікуючи педагогічний процес вцілому. Технологічні новинки допомагають активізувати самомотивацію студентів, їх креативне мислення, самостійність і прагнення до всебічного отримання та засвоєння інформації, стимулюють допитливість та інтерес до наукової діяльності.
Роль мультимедійних технологій у сучасній системі освіти
Роль мультимедийных технологий в современной системе образования
Keywords: комп’ютерні технології; мультимедійні технології; освітній процес; computer technologies; multimedia technologies; educational process; компьютерные технологии; мультимедийные технологии; образовательный процесс